Stochastic model of economic cycles and its econometric application - Karmalita Viacheslav (Data Science in Finance and Economics)
In this paper, I demonstrate the adequacy of economic systems to the basic provisions of synergetics, which makes the latter eligible for macroeconomic analysis. In justifying this statement, a synergetic approach to the development of a model of economic cycles was considered. The novelty of this model was related to the probabilistic description of the investment function and the perception of the economic system as a material object with certain properties. According to the model, the income oscillations are induced by both exogenous (investment fluctuations) and endogenous (system elasticity) causes. The cycle's amplitudes correlate with the intensity of investment fluctuations as well as the efficiency of the economic system. The duration of the economic cycle is determined by the inclusive wealth of the system and its dynamic factor, which characterizes the ability of the system to withstand investment fluctuations and eliminates their consequences. Thus, the economic cycle is interpreted as the 'natural noise' accompanying the functioning of market economics.The proposed model creates a mathematical basis for the numerical analysis of empirical economic data. An example of possible econometric applications of the model was considered using the current cyclic contraction in US incomes.